Formation of polycyclic aromatic hydrocarbons from bimolecular reactions of phenyl radicals at high temperatures. Issue 43 (12th October 2015) - Constantinidis, P.; Schmitt, H.-C.; Fischer, I.; Yan, B.; Rijs, A. M.
Abstract : The self-reaction of the phenyl radical is one of the key reactions in combustion chemistry. Abstract : The self-reaction of the phenyl radical is one of the key reactions in combustion chemistry. Here we study this reaction in a high-temperature flow reactor by IR/UV ion dip spectroscopy, using free electron laser radiation as mid-infrared source. We identified several major reaction products based on their infrared spectra, among them indene, 1, 2-dihydronaphthalene, naphthalene, biphenyl and para -terphenyl. Due to the structural sensitivity of the method, the reaction products were identified isomer-selectively. The work shows that the formation of indene and naphthalene, which was previously considered to be evidence for the HACA (hydrogen abstraction C2 H2 addition) mechanism in the formation of polycyclic aromatic hydrocarbons and soot can also be understood in a phenyl addition model.